G386(P) Combining quality improvement and human factor training to effect sustainable change. (12th March 2018) - Pryde, K; Robson, A; Sykes, K
Abstract : Background: There is evidence to suggest that safety interventions combining quality improvement and team work (systems) training are more effective than those adopting either approach alone. 1 This has important implications for safety and quality improvement (QI) strategies in hospitals. We piloted an initiative combining these factors as a potential model for cascading QI training. We chose the PICU team who already have an annual programme of team training days. Methods: A one day programme was designed consisting of an overview of basic QI methods, an introduction to human factors, and followed by an interactive team treasure hunt with a final session discussing ideas for improvement on PICU. All staff members from domestic to clinical lead, including visiting teams such as psychology and pharmacy were invited to attend. All the improvement ideas were displayed in the staff coffee room and through 'dot-voting' the staff agreed which projects to pursue. Each project identified a nursing and clinical lead from the unit. A combination of facilitated learning sessions on QI tools and techniques appropriate to the projects needs and mentoring was used to support the improvement projects in practice. Results: Approximately 100 staff attended the training days which generated over 20 ideas for improvement. Two projects have been pursued more actively over a year – improving discharge prior to 3 pm and debriefing after significant events. Each has engaged a range of professionals from a spectrum of seniority from the unit. The considerable success of these individual projects is shared separately. Conclusions: This pilot has shown that it is possible to deliver generic training in QI methods and human factors as well as specific improvements through a dedicated project. This has been achieved with no additional time other than the first team training day which was already part of the education programme. The quality improvement methodology and human factor skills are transferrable and have increased the capability of the units' staff to approach future improvement work. We propose this is a cost effective method of effecting real change as well as training in both quality improvement methods and human factors which others should explore adopting. Reference: . McCulloch P, Morgan L, New S, et al. Combining systems and teamwork approaches to enhance the effectiveness of safety improvement interventions in surgery: The safer delivery of surgical services (S3) program. Ann Surg . Ann Surg2017;265:90–96.